As tecnologias na formação docente: uma contribuição no mundo contemporâneo - Lima, Alexandra de Oliveira (2019)
This research had as objective to analyze the contribution of the technologies in the teacher training through a survey of narrative and a qualitative perspective. The reason why this topic was discussed is due to its complexity due to several questions, doubts, possibilities and accesses referring to the process of appropriation of the use of technologies in teacher training, producing a direct relation of work in two ways: teacher / student and student / teacher. The empirical field was the Municipal School Paulo Roberto de Moraes Loureiro and the data were collected together with seven subjects, through a questionnaire that had as objective to characterize personal data, and, later, an interview script. The theoretical basis was constructed from the following authors: Clandinin and Connelly (1999), Pimenta (2012), Veiga and Amaral (2002), Alarção (1996), Tardif (2004) and Nóvoa (1997, 1999, 2010), Kenski (2012, 2013), Lévy (1999), Moran (2013), among others, with regard to teaching narratives, teacher training and technologies in education. The results show that the teachers emphasized that the technologies adhered to in the teacher training contributed substantially to the change in their pedagogical practices in motivating and encouraging learning mainly for the student body. Thus, we can conclude that the technologies inserted in the training bring a relevance to the teacher and its practice in a contemporary world, surrounded by tools and possibilities to be adhered in the school context.